Influência de diferentes níveis de hidratação na qualidade fisiológica e sanitária de sementes de azevém anual (Lolium multiflorum Lam.). - Picoli, Vladimir Adalberto (2005)
The present work had as objective evaluates the answer of the physiologic and sanitary quality of the seeds of annual ryegrass (Lolium multiflorum Lam.) when submitted the combination of periods of times of soak following by dry periods. For a better visualization of the process a curve of soak was established in distilled water, with retreat of samples for determination of the humidity in intervals of 2 hours. The process was driven at room acclimatized with temperature of 25 ºC. The periods of time used were of 5, 10, 15, 20 and 25 hours of interruption of the soak, and the periods of dehydration of 3, 6, 9 and 12 days, with greenhouse use with circulation of air regulated the approximately 28 °C, in a factorial experiment in completely casualizado with 4 repetitions. The determination of the tenor of water for the construction of the curve of soak was made in greenhouse with circulation of air to 105 ºC for 24 hours. The physiologic quality was evaluated through the germination test, accelerated aging and index of germination speed, being used four repetitions of 50 seeds. The analysis of the sanitary quality was executed through the method of paper filter (Blotter test). The results allow to end that periods of soak of 5, 10, 15, 20 and 25 hours following by dry periods of 3, 6, 9 and 12 days don't affect the germination of seeds of azevém-annual. The energy of the seeds of annual ryegrass is less committed as adult is the period of soak up to 25 hours, following by different dry periods. The infestation for Aspergillus sp. it increases in a direct relationship with the time of soak, up to 25 hours, following by a dry period of 12 days, and until 15 hours for the dry periods of 3, 6 and 9 days. The infestation of the seeds for Penicillium sp. it presents a reduction with the increase of the time of soak up to 25 hours, in all of the dry periods.